A Fresh Look at the Dark Side of Contemporary Careers: Toward a Realistic Discourse. (8th June 2015) - Baruch, Yehuda; Vardi, Yoav
Abstract : In this paper we propose that careers be considered as both offering promise and the source of potential disillusionment. While the changing nature of careers and of career management requires a comprehensive perspective to highlight the characteristics and nature of careers in their entirety, most published work predominantly addresses the positive aspects of careers, leaving their darker dynamics almost untouched. We argue that while career scholars tend to clothe such concerns in euphemistic terms, contemporary career experiences may often be quite dark and include a number of undesired consequences. By linking selected career constructs and notions of organizational dark sides, we aim to advance a more balanced framework, offering a career perspective that consists of opportunities versus threats, truth versus untruth and positive versus negative aspects, all of which are inevitably embedded in careers. Thus, we call for career conceptualization and research to be less normatively biased and prescriptive and to be more grounded in reality.